1993
DOI: 10.1115/1.2930329
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modal Multifurcation With International Resonance: Part 1—Deterministic Approach

Abstract: The bifurcation and multifurcation in multimode interaction of nonlinear continuous structural systems is investigated. Under harmonic excitation the nonstationary response of multimode interaction is considered in the neighborhood of fourth-order internal resonance condition. The response dynamic characteristics are examined via three different approaches. These are the multiple scales method, numerical simulation, and experimental testing. The model considered is a clamped-clamped beam with initial static ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A deterministic beam test specimen [8] was installed on the shaker platform such that torsional and out-of-plane motions were minimized. Adjusting the initial axial load P = 2.76 lb for internal resonance was difficult because the clamped ends affected the setting.…”
Section: Experimental and Adams Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A deterministic beam test specimen [8] was installed on the shaker platform such that torsional and out-of-plane motions were minimized. Adjusting the initial axial load P = 2.76 lb for internal resonance was difficult because the clamped ends affected the setting.…”
Section: Experimental and Adams Resultsmentioning
confidence: 99%
“…Using Galerkin's method the PDE governing equation is reduced to three ordinary differential equations of motion by substituting the assumed mode solutions for U(z, t) and requiring the equation to be orthogonal to a selected mode shape [8]. The modal expansion is given as…”
Section: Galerkin's Methods Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Imposing appropriate assumptions, it is shown that the problem is fundamentally reduced to a nonlinear Leipholz beam subjected to two frequency excitations of the moving contact loads. There have been a number of theoretical and experimental studies on the chaotic vibration of a forced beam element, e.g., [24][25][26][27][28][29]. In these reports, various techniques such as multiple scales and direct numerical integration have been employed to simulate the chaotic motions.…”
Section: Introductionmentioning
confidence: 99%